Development and content validation of a symptom assessment for eosinophilic gastritis and eosinophilic gastroenteritis in adults and adolescents - Calvin N. Ho (BMC, 2021)
Abstract Background A patient reported outcome (PRO) instrument with evidence of validity and reliability for assessing symptoms of eosinophilic gastritis (EG) and eosinophilic gastroenteritis (EGE) is needed to measure treatment benefit in clinical trials. The aim of this research is to develop an EG/EGE symptom PRO instrument for patients aged 12 and above. Methods The Symptom Assessment for Gastrointestinal Eosinophilic Diseases (SAGED) was developed through a literature review, discussions with expert clinicians, and concept elicitation and cognitive debriefing interviews with patients. Patients (n = 28) were recruited based on confirmed diagnosis and self-reported symptoms. The final instrument was translated and linguistically validated with additional cognitive debriefing interviews (n = 105). Results SAGED is a 24-h recall questionnaire consisting of eight items evaluating the core symptoms of EG and EGE (abdominal pain, nausea, bloating, early satiety, loss of appetite, vomiting, and diarrhea). Seven of the eight items are evaluated on an 11-point numerical rating scale ranging from ‘none’ to ‘worst imaginable’. Cognitive debriefing interviews showed that adults and adolescents understand the content and are able to select a response that reflects their experience. The linguistic validation process produced 21 translations that are understandable to patients and conceptually equivalent to the source version. Conclusions SAGED is suitable for measuring symptom improvement in adult and adolescent patients with EG and/or EGE. The content validity of SAGED has been established through best practices in qualitative research for PRO instrument development. The psychometric properties of SAGED will be evaluated in a future study.